2019
DOI: 10.1007/s00384-019-03349-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled study of preoperative oral carbohydrate loading versus fasting in patients undergoing colorectal surgery

Abstract: Purpose This study aimed to evaluate the effect of preoperative carbohydrate oral (CHO) loading on the postoperative metabolic and inflammatory response, perioperative discomfort and surgical clinical outcomes in open colorectal surgery compared with a conventional fasting protocol. Methods Fifty patients were randomly allocated to either the intervention group (CHO), to receive preoperative oral carbohydrate supplementation, or the control group (FAST), to undergo preoperative fasting. Insulin resistance, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 35 publications
0
48
1
14
Order By: Relevance
“…As shown in some prior trials [16,25,28], our study also found that the GDFT protocol is associated with reductions in the rate of postoperative complications. In addition, the lower incidence of postoperative infection complications in the GDFT group may also be related to preoperative oral carbohydrate loading, which may reduce the metabolic and in ammatory response after surgery and improved surgical clinical outcomes [29]. However, the rates of postoperative complications in some previous studies were higher than in our present analysis.…”
Section: Discussioncontrasting
confidence: 60%
“…As shown in some prior trials [16,25,28], our study also found that the GDFT protocol is associated with reductions in the rate of postoperative complications. In addition, the lower incidence of postoperative infection complications in the GDFT group may also be related to preoperative oral carbohydrate loading, which may reduce the metabolic and in ammatory response after surgery and improved surgical clinical outcomes [29]. However, the rates of postoperative complications in some previous studies were higher than in our present analysis.…”
Section: Discussioncontrasting
confidence: 60%
“…In addition, we only monitored the incidence of postoperative complications that occurred during hospitalization, whereas Benes et al monitored patients for 30 days [25]. Lastly, the lower incidence of postoperative complications in our study may also be related to preoperative oral carbohydrate loading, which may reduce the metabolic and inflammatory response after surgery and improved surgical clinical outcomes [27]. Together, our results suggest that perioperative fluid optimisation reduces the incidence of postoperative complications in elderly patients, rather than only in high-risk patients.…”
Section: Discussionmentioning
confidence: 84%
“…EDIA initiated earlier postoperative oral feeding as per ERAS recommendation. Majority of EDIA received intensive nutritional intervention where they were not only received the energy-dense clear uid ONS preoperative 3-hours but also energy-dense clear uid ONS postoperative once started clear uid and followed by energy-dense complete ONS after allowing solid diet while most of DDIA received plain water after allowed for clear uid, nourishing uid and followed by soft diet [29]. Postoperative intensive nutritional intervention management aimed to prevent nutritional depletion due to negative energy protein balance, maintain an appropriate nutritional status to support rehabilitation and wound healing [31].…”
Section: Discussionmentioning
confidence: 99%
“…These approaches minimize the energy protein negative balance, provide early energy protein supply, reduce protein loss, improve muscle function, and promote the anabolic state. Preservation of postoperative weight loss and muscle wasting could be achieved by minimizing body glycogen breakdown, glucose synthesis from protein or fat, and fat oxidation [29]. The body composition and handgrip strength conservations might result from the combined effect of shortening of preoperative fasting and postoperative early feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation